174k views
1 vote
Whats the average rate of change from x = - 3 to x = 5

Whats the average rate of change from x = - 3 to x = 5-example-1

1 Answer

2 votes

Answer:

0

Explanation:

Average rate of change from x = -3 to x = 5.

When x = -3, y = -1. That is f(-3) = -1

When x = 5, y = -1, That is f(5) = -1

Average rate of change =
(f(b) - f(a))/(b - a)

Where,


a = -3, f(a) = -1


b = 5, f(b) = -1

Plug in the values into the equation:


= (-1 - (-1))/(6 -(-3))


= (0)/(8)


= 0

Average rate of change = 0

User Matt Denwood
by
6.7k points